The effect of the using waste marble dust as fine sand on the mechanical properties of the concrete - Demirel, Bahar (Academic Journals, 2010)
In this experimental study, the effects of using waste marble dust (WMD) as a fine material on the mechanical properties of the concrete have been investigated. For this purpose four different series of concrete-mixtures were prepared by replacing the fine sand (passing 0.25 mm sieve) with WMD at proportions of 0, 25, 50 and 100% by weight. In order to determine the effect of the WMD on the compressive strength with respect to the curing age, compressive strengths of the samples were recorded at the curing ages of 3, 7, 28 and 90 days. In addition, the porosity values, ultrasonic pulse velocity (UPV), dynamic modulus of elasticity (E(din)) and the unit weights of the series were determined and all data were compared with each other. Finally, all of the data were compared with each other. It was observed that the addition of WMD such that would replace the fine material passing through a 0.25 mm sieve at particular proportions has displayed an enhancing effect on compressive strength. Marble dust is a by-product of marble production facilities and also creates large scale environmental pollution. Therefore, it could be possible to prevent the environmental pollution especially in the regions with excessive marble production and to consume fewer natural resources as well through its utilization in normal strength concretes as a substitute for the very fine aggregate.
Keywords: Waste marble dust; very fine sand; concrete; dynamic modulus of elasticity; compressive strength; sorptivity